Glenoid Dysplasia - Randall, Terry (1995)
Athletic trainers evaluate many athletes with acute and chronic shoulder problems such as rotator cuff pathology, impingement syndromes, and inflammatory conditions. They also need to be aware of more obscure reasons for shoulder pain and dysfunction. The purpose of this paper is to describe a rare congenital abnormality called glenoid dysplasia, which can be responsible for a variety of shoulder complaints in athletes. Characteristics of glenoid dysplasia are seen on radiographs and include a shallow glenoid fossa and a hypoplastic scapular neck. This case study depicts an athlete who functioned at a very high level for many years before developing symptoms. This athlete was able to continue an active lifestyle but some limitations were recommended.